ISLAMIC PERSPECTIVE IN THE FULFILLMENT OF PRISONERS' HEALTH RIGHTS AS A GOVERNMENT RESPONSIBILITY - B, Burhanuddin; M, Maskawati; M, Andriani (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study aims to determine the government's responsibility in fulfilling the rights to health services for prisoners. The primary data in this study were obtained through an empirical (nondoctrinal) approach in Watampone Class IIA Prison and analyzed qualitatively descriptively in an Islamic perspective based on the theory of Maqoshid Al Shari'ah. The results showed that state responsibility is a constitutional obligation of the state, especially the government to strive for the fulfillment of prisoners' rights. In the conception of Hifz al Nafs, this responsibility is a form of protection / safeguarding the human soul not only for the general public but also for prisoners (prisoners) with the fulfillment of their rights as human beings.Penelitian ini bertujuan untuk mengetahui tanggung jawab pemerintah dalam pemenuhan hak pelayanan kesehatan narapidana. Data primer dalam penelitian ini diperoleh melalui pendekatan empirik (nondoktrinal) pada Lapas Kelas IIA Watampone dan dianalisis secara deskriptif kualitatif dalam perspektif Islam yang bertumpu pada teori Maqoshid Al Syari’ah. Hasil penelitian menunjukkan bahwa tanggung jawab negara merupakan kewajiban konstitusional negara terutama untuk mengupayakan pemenuhan hak-hak narapidana. Dalam konsepsi Hifz al Nafs, tanggung jawab ini merupakan bentuk perlindungan/menjaga jiwa manusia bukan saja bagi masyarakat umum tetapi juga bagi warga binaan pemasyarakatan (narapidana) dengan jalan pemenuhan hak-haknya sebagai manusia.